Keindahan yang Semu: Analisis Dekonstruksi Derrida - Nesa Riska Pangesti; Candra Rahma Wijaya Putra; Fina Hiasa; Yeni Yulia Andriani (Faculty of Languages and Arts, Universitas Negeri Padang, 2022)
This research is motivated by the problems of beauty and normality that develop in society. Women are often seen as objects that must be judged and contested for their beauty. Beautiful and normal is considered a solid and patent construction. However, the meaning of beautiful and normal is not stable. The purpose of this study is to deconstruct the structure that is considered to be established regarding beauty and normality. The method used to deconstruct this structure is the deconstruction method offered by Derrida. The data source of this research is the novel Maya by Ayu Utami, while the data in this study are words, phrases, sentences, and paragraphs that contain discourses of beauty and normalcy in the novel Maya. Furthermore, data analysis is carried out through the study of binary oppositions to then look for the hierarchical structure in the binary oppositions. After obtaining the binary opposition and hierarchical structure, then the deconstruction process is carried out. The results obtained in this study include the normative structure of beauty and normality in the novel Maya, binary opposition in the novel Maya, and the deconstruction of beauty and normal in the novel Maya.